2019
DOI: 10.1371/journal.pone.0226478
|View full text |Cite|
|
Sign up to set email alerts
|

An explorative study identifies miRNA signatures for the diagnosis of non-celiac wheat sensitivity

Abstract: Non-celiac wheat sensitivity (NCWS), also referred to as non-celiac gluten sensitivity, is a recently described disorder triggered by wheat/gluten ingestion. NCWS elicits a wide range of symptoms including diarrhoea, intestinal discomfort, and fatigue in analogy with other wheat/gluten-related disorders and celiac disease in particular. From the pathological standpoint, NCWS patients only have a slight increase of intraepithelial lymphocytes, while antibodies to tissue transglutaminase (tTG) and villous atroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…The pathogenesis of NCGS/WS is still uncertain; a higher intestinal expression of toll-like receptors suggesting a stronger implication of the innate immune mechanisms, the infiltration of immune cells in the gut mucosa, increased expression of antibodies, and dysregulated gene expression profiling and epigenetic mechanisms have been described [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Furthermore, impaired intestinal barrier and permeability and gut dysbiosis have been advocated as key factors by several studies [ 1 , 2 , 4 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of NCGS/WS is still uncertain; a higher intestinal expression of toll-like receptors suggesting a stronger implication of the innate immune mechanisms, the infiltration of immune cells in the gut mucosa, increased expression of antibodies, and dysregulated gene expression profiling and epigenetic mechanisms have been described [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Furthermore, impaired intestinal barrier and permeability and gut dysbiosis have been advocated as key factors by several studies [ 1 , 2 , 4 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the double-blind placebo-controlled (DBPC) crossover gluten challenge test, which remains at present the gold standard test for NCGS/WS diagnosis, is cumbersome and not easy to perform in daily clinical practice. Indeed, many studies referred to self-reported diagnosis [ 3 , 9 , 10 , 13 , 17 ], but only 8% to 34% of the individuals with self-reported gluten sensitivity worsened their symptoms after gluten ingestion, thus suggesting that self-reporting overemphasized the syndrome [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study by our laboratory we identified seven miRNA (hsa-miR-19b-3p, hsa-miR-19a-3p, hsa-miR-186-5p, hsa-miR-17-5p, hsa-miR-145-5p, hsa-miR-30e-5p, and hsa-miR-143-3p) whose expression was higher in the intestinal mucosa of NCWS patients than in controls with dyspeptic symptoms or celiac disease ( 60 ). Remarkably, six of these miRNA were also dysregulated in peripheral blood leukocytes of NCWS.…”
Section: Gene and Microrna Expression Is Dysregulated In The Small Inmentioning
confidence: 95%
“…Furthermore, evidence was provided for an overexpression of selected miRNA in the intestinal mucosa and peripheral blood leukocytes (PBLs) of NCWS patients if compared to symptomatic controls with functional dyspepsia or CD. Hsa-miR-30e-5p proved to be the best predictor of NCWS vs. CD in biopsies and vs. controls in PBLs [ 154 ]. The absence of validated diagnostic criteria also explains the high rate of self-diagnosis [ 155 , 156 ] as well as the impact of patients’ perception of symptoms and of the nocebo effect on the interpretation of study results [ 157 ].…”
Section: Gluten-related Disordersmentioning
confidence: 99%